What can we learn from senescent platelets, their transcriptomes and proteomes?. (31st December 2023) - Allan, Harriet E.; Vadgama, Ami; Armstrong, Paul C.; Warner, Timothy D.
Abstract: Research into the natural aging process of platelets has garnered much research interest in recent years, and there have long been associations drawn between the proportion of newly formed platelets in the circulation and the risk of thrombosis. However, these observations have largely been demonstrated in patient groups in which there may be underlying systemic changes that effect platelet function. Recent advances in technology have allowed in-depth analysis of differently aged platelets isolated from the peripheral blood of healthy individuals and have demonstrated that aged platelets, often referred to as senescent platelets, undergo extensive changes in the transcriptome and proteome. Ultimately, these changes result in platelets whose functions have deteriorated such that they cannot partake in hemostatic responses to the same extent as newly formed platelets. Here, we review transcriptomic and proteomic research in platelet aging in the context of health and how this research sheds light upon alterations in platelet structure and function. Plain Language Summary: Platelets normally last within the human circulation for approximately 10 days, however there are a number of diseases in which this life span is notably reduced. People who have platelets with such reduced lifespans have higher risks of heart attacks and strokes and reduced responsiveness to standard anti-platelet drugs. Research in recent years has aimed to understand the age-related changes that occur within platelets as they circulate in the bloodstream. In this review article, the authors provide a summary of the changes that occur during the natural aging process of platelets in healthy people, highlighting reductions in the levels of RNA and proteins. Despite these general reductions in their own RNA and proteins, research has shown that as platelets circulate they take up other RNA transcripts and proteins from the bloodstream, and this too seems a hallmark of platelet aging. The authors also discuss age-related declines in various aspects of platelet function which renders them less effective participants in the formation of blood clots.